Optimizing the Economic Independence of Sharia-Based Islamic Boarding Schools - Anwar, Mustofa; Wijaya, Toni; Rialita, Agnes Jevi; Zahro, Luluatuz (Jurnal Internasional Ekonomi Islam, 2024)
Introduction: The independence of Islamic Boarding Schools is a necessity because pesantren can be seen through the process of establishing pesantren which usually uses Kiyai's funds and assistance from the surrounding community. The irony is that there are still many pesantren that still depend on the injection of outside funds. Objectives: This study aims to find out how business strategies are applied to the Islamic Boarding School of Darul A'mal Lampung to accelerate the economic independence of sustainable Islamic Boarding School. Method: By using qualitative research methods and case study approaches (field research). Data were obtained through direct observation, and in-depth interviews with related parties (Foundation administrators, heads of cottage business units, teachers, and students). Results: The findings in this study are steps to optimize the pesantren business that can be done to realize the independence of pesantren optimally by strengthening pesantren management, optimizing existing business potential, expanding cooperation, and opening public spaces in terms of business, improving the ability of human resources in sharia-based business management. Implications: This study reaffirms the steps that can be taken to optimize the independence of pesantren through strengthening pesantren management, equalizing the perceptions of all pesantren stakeholders about the vision and mission of pesantren, together continuing to learn by providing training, as well as implementing policies well and followed by in-depth evaluation on an ongoing basis. So that the results of this research can be used as a reference for optimizing the pesantren business in realizing sustainable pesantren independence.